Pengaruh Pendidikan Ekonomi Dalam Keluarga, Literasi Keuangan Dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa Universitas Sebelas Maret Surakarta - Fitri Wulandari; Dewi Kusuma Wardani; Feri Setyowibowo (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2021)
The aims of this study is to determine the effect of economic education in the family, financial literacy and lifestyle on the consumptive behavior of students at Sebelas Maret University Surakarta. The determination of research method is descriptive quantitative with research subjects totaling 395 respondents. The sampling technique is done by probability sampling. Data was collected by means of a questionnaire. The results show that; (1) economic education in the family, financial literacy and lifestyle have a significant effect on the consumptive behavior of students at Sebelas Maret University Surakarta as evidenced by the results of the f test is 49,068 > 2.63. (2) economic education in the family has a negative and significant effect on the consumptive behavior of students at Sebelas Maret University, Surakarta, as evidenced by the results of the t test is -3.144 > 1.966. (3) financial literacy has a negative and significant effect on the consumptive behavior of students at Sebelas Maret University Surakarta, as evidenced by the results of the t test is -2.202 > 1.966. (4) lifestyle has a positive and significant effect on the consumptive behavior of students at Sebelas Maret University Surakarta, as evidenced by the results of the t test is 11.224 > 1.966.